Experimental Investigation on Material Transfer Mechanism in WEDM of Pure Titanium (Grade-2) - Anish Kumar; Vinod Kumar; Jatinder Kumar (Advances in Materials Science and Engineering)
This research work mainly focused on experimental investigation on material transfer mechanism in WEDM of pure titanium. The effects of machining parameters such as pulse on time, pulse off time, peak current, spark gap voltage, wire feed, and wire tension on the material removal rate (MRR), overcut, and surface roughness for pure titanium in WEDM process were explored. The selected machined samples were analyzed using energy dispersive X-ray analysis, scanning electron microscope, and X-ray diffraction techniques. It was observed from the results that a significant material transfer occurred from the dielectric, as well as tool, electrode on the work surface either in free form and/or in compound form. Also the multiresponse optimization of process parameters was done using desirability approach. The predictions from this model were validated by conducting experiments.